Rancang Bangun Alat Kempa Panas Dingin Berbasis PLC Untuk Pengolahan Sabut Kelapa Menjadi Parket Sebagai Upaya Peningkatan Nilai Ekonomis Limbah Sabut Kelapa - Sujana, Ivan; Prawatya, Yopa Eka; Lestari, Retno Budi (Faculty of Engineering, Universitas Tanjungpura, 2014)
Abstract This research aimed to design and construct PLC based press machine to produce parquet from coco fiber in accordance with the Indonesian National Standard (SNI 01-4449-2006). Researchers conducted a factorial experiment on the composition of the material forming the parquet to have been a factor in the study of high density < 0.84 g/cm3 and medium density factor is 0.40g/cm3 to 0.84 g/cm3. Next step is designing the construction and workings of PLC based parquet press machine, mold the parquet and conduct testing molded parquet products based on the guidelines of the National Standards Agency (BSN) on standard fiber board is SNI 01-4449-2006 . Based on the test results of density, parquet generated by the composition of 50% coco fiber with 50% adhesive and filler classified as High Density Fiberboard and parquet with composition of 65% coco fiber with a 35% mixture of adhesive and filler classified as Medium density Fiberboard. Based on tests of water absorption and water content, parquet with a composition of 35% coco fiber with 65% adhesive and filler or parquet with composition of 50 % coco fiber with 50 % adhesive and filler has been able to meet the requirement . Based on the thick expansion test , only parquet with code C3-IK6 and C3-IK9 qualified to the category of medium density fiberboard. Based on the tensile test perpendicular surface firmness, parquet printout for the composition 35 % coco fiber with 65 % adhesive and filler, and the composition of 50% coco fiber with 50% adhesive and filler has a surface perpendicular firmness pull more than 1.5 kgf/cm2 thus meeting the requirements. Based on the constancy test flexural fracture (MOR) and modulus of elasticity firmness (MOE), test of parquet in this research meet the requirements of SNI No. 01-4449-2006 to the category of medium density fiberboard Type 15. Keywords Parquet, coco fiber, design, fiber board